Lymphocytic gastritis and coeliac disease: evidence of a positive association - K M Feeley; Michael A. Heneghan; F. M. Stevens; Colm McCarthy (1998)
To investigate the prevalence of lymphocytic gastritis in patients with coeliac disease.Gastric biopsies from 70 patients with coeliac disease were examined by light microscopy for the presence of lymphocytic gastritis, defined as 25 or more intraepithelial lymphocytes/100 gastric columnar epithelial cells.Lymphocytic gastritis was found in seven cases. Positive cases had a mean of 32.1 intraepithelial lymphocytes/100 columnar cells, compared with a mean of 13.9 in negative cases, and 5.15 in noncoeliac controls. No differences were found for age, sex, gastric corpus or antrum, or degree of inflammation in the gastric lamina propria. All intraepithelial lymphocytes were of T cell lineage. Cases not showing lymphocytic gastritis did however show significantly increased gastric intraepithelial lymphocytes compared with non-coeliac controls. Eighteen of 70 cases were positive for Helicobacter pylori, and four of seven cases of lymphocytic gastritis were H pylori positive; no significant difference was observed between H pylori positive and negative patients. Three cases had concomitant ulcerative enteritis, of which none showed lymphocytic gastritis, while five cases had concomitant enteropathy associated T cell lymphoma, of which one showed lymphocytic gastritis.Lymphocytic gastritis occurred in 10% of patients with coeliac disease. Cases without lymphocytic gastritis nevertheless showed increased gastric intraepithelial lymphocytes. Coeliac disease may on occasion be a diffuse lymphocytic enteropathy occurring in response to gluten. Lymphocytic gastritis outside coeliac disease may involve an immune response to luminal antigens, such as H pylori, not unlike the response to gluten in patients with coeliac disease.